STUDENTS’ PERCEPTIONS TOWARD THE USE OF GOOGLE TRANSLATE IN TRANSLATING - Selfian Tumbal; Nihta V.F. Liando; Sanerita T Olii (KOMPETENSI, 2021)
This study aims to reveal students’ perception toward the use of google translate in translating at English Education Department, Universitas Negeri Manado. This research was a quantitative research and descriptive method is applied. A questionnaire that consists of 17 items was used as an instrument to collect the data. The questionnaire employed Likert scale. The sample was 30 eighth semester students of English Education Department Universitas Negeri Manado. The collected data were quantitative and analysed with percentage formula. Based on the findings, almost all statements received positive responses from the respondents. There were 2 statements that had higher responses which number 1 and 6. There were 93.3% of respondents agreed that they were interested in translating activity and used google translate as a media in translating, furthermore 80% of respondents agreed that they can translate easier using google translate. It means that the 8th semester students of English Education Department in Universitas Negeri Manado like the activity of translating and they do the translation easier using Google Translate. In addition, the average of the positive response in the other questionnaire items were above 50%. on the other hand, 40.3% of the respondents disagreed about the statement “google translate can translate paragraph by paragraph effectively”, 60% of respondents agreed that google translate made them lazy to open dictionary. Thus it can be concluded that google translate was helpful in translating especially translating English to Indonesian, furthermore the students are suggested to re-check the result of google translate and to not rely totally on it.